Acute management of priapism in men - Tay, Yeng K.; Spernat, Daniel; Rzetelski‐West, Kathryn; Appu, Sree; Love, Chris (BJU international, 2012)
What's known on the subject? and What does the study add? Priapism is a rare event. However, various medications and medical conditions may increase the risk. Priapism can be ischaemic, non‐ischaemic or stuttering. It is paramount to distinguish the type of priapism, as misdiagnosis may lead to significant morbidity. Ischaemic priapism represents a compartment syndrome of the penis and is therefore a medical emergency. A delay in management may significantly affect future erectile function. Stuttering priapism represents recurrent subacute episodes of ischaemic priapism, which may lead to erectile dysfunction. Thus episodes must be minimised. Non‐ischaemic priapism is not a medical emergency. However, misdiagnosis and injection with sympathomimetic agents can result in system absorption and toxicity. This review article provides a summary of the evaluation and management of priapism. Furthermore, a step by step flow chart is provided to guide the clinician through the assessment and management of this complex issue. OBJECTIVES • To review the literature regarding ischaemic, non‐ischaemic and stuttering priapism • To provide management recommendations PATIENTS AND METHODS • A Medline search was carried out to identify all relevant papers with management guidelines for priapism. RESULTS • Ischaemic priapism represents a compartment syndrome of the penis and urgent intervention is required to decrease the risk of erectile dysfunction. • Non‐ischaemic priapism is not a medical emergency; however, it can result in erectile dysfunction. • The treatment objective for stuttering priapism is to reduce future episodes with systemic treatments, whilst treating each ischaemic episode as an emergency. CONCLUSIONS • Priapism is a complex condition that requires expert care to prevent complications and irreversible erectile dysfunction